2015
DOI: 10.1128/aac.05014-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Novel Sublingual Spray Formulation of the Antimalarial Drug Artemether in African Children with Malaria

Abstract: A lthough parenteral artesunate is the recommended initial treatment for severe malaria (1), intramuscular (i.m.) artemether is an acceptable and practical alternative (1, 2). Artemether is also a recommended first-line oral therapy in combination with the longer half-life partner drug lumefantrine for uncomplicated Plasmodium falciparum (3) and Plasmodium vivax (4) infections. There are, however, few detailed studies assessing the pharmacokinetics of artemether and its active metabolite dihydroartemisinin (DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This notion has been challenged by a report indicating that NALT DCs possess the machinery for induction of RA and expression of α4β7+ on effector B cells, but stimulation by microbiota was required for these functions to develop (46). The sublingual route is used effectively for delivery of medication and allergen-specific immune therapy in humans and animals (4750). This route has recently emerged as a mode of vaccine delivery capable of eliciting both systemic and mucosal immune responses while avoiding many of the side effects and formulation concerns associated with oral or intranasal vaccination (5153).…”
Section: Vaccine Adjuvants and Delivery Systems For Induction Of Mmentioning
confidence: 99%
“…This notion has been challenged by a report indicating that NALT DCs possess the machinery for induction of RA and expression of α4β7+ on effector B cells, but stimulation by microbiota was required for these functions to develop (46). The sublingual route is used effectively for delivery of medication and allergen-specific immune therapy in humans and animals (4750). This route has recently emerged as a mode of vaccine delivery capable of eliciting both systemic and mucosal immune responses while avoiding many of the side effects and formulation concerns associated with oral or intranasal vaccination (5153).…”
Section: Vaccine Adjuvants and Delivery Systems For Induction Of Mmentioning
confidence: 99%
“…In addition, the nausea and vomiting associated with a febrile illness, such as malaria, which can be exacerbated by oral dosing with fluids or food, are less of a barrier to treatment with sublingual administration. ArTiMist (Essential Nutrition Ltd., Brough, England) is a sublingual formulation of artemether in neutral oil that is administered as a metered sublingual spray and which is being developed as a candidate for prereferral treatment, especially in young children (see the accompanying paper [19]). In the present study, the first of two pharmacokinetic evaluations of this product, the disposition of ArTiMist relative to that of single-dose oral artemether given as tablets, as well as its multidose pharmacokinetics, were examined in healthy adult volunteers.…”
mentioning
confidence: 99%
“…The present study was conducted in two parts. Study (10,11). The present paper provides details of the trial procedures and efficacy and safety outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacokinetic analysis shows that ArTiMist is promptly and adequately absorbed regardless of the indices of severity, including consciousness level, and even in patients with a history of vomiting at presentation (11). Simulations demonstrated that sublingual artemether bioavailability (artemether and dihydroartemisinin [DHA]) was at least equivalent to that after conventional artemether-lumefantrine oral therapy in older Melanesian children with uncomplicated malaria (11).…”
Section: Efficacy Of Sublingual Artemether In Childrenmentioning
confidence: 99%
See 1 more Smart Citation